Nonoverweight nonalcoholic fatty liver disease and incident cardiovascular disease: A post hoc analysis of a cohort study. Issue 18 (May 2017) - Yoshitaka, Hashimoto; Hamaguchi, Masahide; Kojima, Takao; Fukuda, Takuya; Ohbora, Akihiro; Fukui, Michiaki
Abstract : Abstract: Nonalcoholic fatty liver disease (NAFLD) is known as a risk of incident cardiovascular disease (CVD). About 20% of NAFLD occurs in nonobese individuals. However, it remains to be elucidated the association between nonoverweight with NAFLD and a risk of incident CVD. Therefore, we investigated the risk of nonoverweight with NAFLD for incident CVD. We performed a post-hoc analysis of the previous prospective cohort study, in which 1647 Japanese were enrolled. Abdominal ultrasonography was used to diagnose NAFLD. Overweight was defined as body mass index ≥23 kg/m 2, which is recommended by World Health Organization for Asian. We divided participants into 4 phenotypes by existence of NAFLD and/or overweight. The hazard risks of the 4 phenotypes for incident CVD were calculated by Cox hazard model after adjusting for age, sex, smoking status, exercise, hypertension, hyperglycemia, hypertriglyceridemia, and low high-density lipoprotein cholesterol at baseline examination. Incident proportions of CVD were 0.6% in nonoverweight without NAFLD, 8.8% in nonoverweight with NAFLD, 1.8% in overweight without NAFLD, and 3.3% in overweight with NAFLD. Compared with nonoverweight without NAFLD, the adjusted hazard ratios of incident CVD were 10.4 (95% confidence interval 2.61–44.0, P = .001) in nonoverweight with NAFLD, 1.96 (0.54–7.88, P = .31) in overweight without NAFLD, and 3.14 (0.84–13.2, P = .09) in overweight with NAFLD. Nonoverweight with NAFLD was associated with higher risk of incident CVD. We should pay attention to NAFLD, even in nonoverweight individuals, to prevent further CVD events.